Light Detection and Ranging in the Geomorphological Characterization of the Coast Dunes Field of Rio Do Fogo, Rio Grande Do Norte, Brazil - de Souza Matos-Carneiro, Márcia Cristina; Ferreira, Bruno; Gregorio, Maria das Neves; Pessanha, Pessanha; Lins da Silva, Dyêgo; de Oliveira-Vital, Saulo Roberto (Revista Geográfica de América Central., 2018)
The objective of this study was to understand the dynamics of the geomorphological evolution of the dune field of Rio do Fogo, State of Rio Grande do Norte, Brazil. For that, a geomorphological map of the study area was elaborated, whose cartographic base (Dot Cloud images and Digital Terrain Model - MDT) originated from the airborne laser mapping of the LIDAR (Light Detection and Ranging) Airborn system. The images generated by the points of the laser scanning sensor were able to characterize the geomorphology of the dune field of the research area, using the wind conservation and / or dissection present in the area as a classification criterion, identifying the morphostructural units and their respective Morphosculptures. Based on the degree of morphological conservation, two very distinct morphological groups were identified: (a) a Dunar Windfall Accumulation Plain; and (b) a Scheduling Windfall Accumulation Plain (PAER). These two morphoscultured Aeolian sets were elaborated along the late Pleistocene, with depositional activity until the transition to the Holocene.